2020
DOI: 10.1021/acs.inorgchem.0c01630
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Stability and Ligand Substitution of a Layered Cu(I)/Isocyanide-Based Organometallic Network Material with a Well-Defined Channel Structure

Abstract: Isocyanide coordination networks (ISOCNs), which consist of multitopic isocyanide linker groups and transition-metal-based secondary building units (SBUs), are a promising class of organometallic framework materials for the inclusion of low-valent metal centers as primary structural components. Previously, it was demonstrated that the ditopic m-terphenyl isocyanide ligand, [CNArMes2]2 (ArMes2 = 2,6-(2,4,6-Me3C6H2)2C6H3), could provide single-metal node frameworks based on Cu­(I) and Ni(0) centers. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 81 publications
4
13
0
Order By: Relevance
“…Importantly, Fourier transform infrared (FTIR) analysis revealed a sharp ν CN band centered at 2155 cm −1 . As we have previously shown for both molecular copper(I) tris(isocyanide) complexes 42 and isocyanide networks featuring copper(I) tris(isocyanide) SBUs, 26,28 such a high-energy ν CN band is diagnostic of a cationic [(L)Cu(CNR) 3 ] + coordination environment, where the fourth L-type ligand is a weak σ donor. In the presence of stronger σ donors, a distinctive shift of ν CN to lower energy is observed because of greater Cu p-orbital participation in bonding.…”
Section: ■ Results and Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Importantly, Fourier transform infrared (FTIR) analysis revealed a sharp ν CN band centered at 2155 cm −1 . As we have previously shown for both molecular copper(I) tris(isocyanide) complexes 42 and isocyanide networks featuring copper(I) tris(isocyanide) SBUs, 26,28 such a high-energy ν CN band is diagnostic of a cationic [(L)Cu(CNR) 3 ] + coordination environment, where the fourth L-type ligand is a weak σ donor. In the presence of stronger σ donors, a distinctive shift of ν CN to lower energy is observed because of greater Cu p-orbital participation in bonding.…”
Section: ■ Results and Discussionsupporting
confidence: 61%
“…These spectroscopic features agree well with previously reported mono-and ditopic mterphenyl isocyanides. 26,28,30 Crystallographic structural determination of TIB Mes2 H revealed that it is indeed an asymmetric rigid linear organoisocyanide containing a benzoic acid group. In the solid state, the benzoic acid group is canted ∼33°r elative to the Ar Mes2 unit (Figure S5.1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations